The effect of spraying with Zolfast on some physical qualities of three hybrids of eggplant solanum melongena L. growing under protected cultivation - Batool Hanoon Falih Al_Zubaidy; Sabaa Aodah Hsabah (University of Thi-Qar Journal of agricultural research, 2022)
The current study was conducted in the plastic House during the growing season 2021_2022 at the research station belonging to the Faculty of Agriculture and marshes / Dhi Qar University / mustafiya area in order to study the effect of spraying with Zolfast on the growth and yield of three hybrids of eggplants and the overlap between them under protected cultivation (plastic house ), the varieties (black,Barcelona and Black Beauty) were planted ,where they were treated with five concentrations(0, 0.5, 1, 1.5 and 2) MLL1, and spraying five sprays and every two weeks a spray, and its effect on the physical qualities (number, weight, length and diameter of the fruit) of the eggplant plant was studied. Use the design of complete random sectors (R.C.B.D) for a one-time split factor experiment, where the items are placed in the main pieces of the Main_Plot and the concentration of zolfast is the second factor of the Sup_Plot, where it was distributed to three repeaters for each item in one warehouse, thus the number of experimental units reached 45 units . And the adoption of statistical analysis of results using the SPSS system and the L test.S.D to test the averages at the probability level of 0.05 (narrator and khalafullah, 2000). The results showed the superiority of the Barcelona variety in terms of the number of fruits and their length, as it reached (25.12) plant fruit-1, (16.90)CM fruit-1, respectively, and the superiority of the Black Beauty variety in terms of fruit weight by (202.63) G fruit-1 per experimental unit . The Barcelona variety exceeded the diameter of the fruit and reached a value of (6.53) CM fruit -1.